2004
DOI: 10.1677/joe.0.1810515
|View full text |Cite
|
Sign up to set email alerts
|

Differential responses of the hypothalamo-pituitary-adrenocortical axis to acute restraint stress in Hatano high- and low-avoidance rats

Abstract: The high-and low-avoidance animal (HAA and LAA respectively) strains of Hatano rats were originally selected and bred from Sprague-Dawley rats for their performance in the shuttle-box task. The present study focused on the activity of the hypothalamo-pituitary-adrenocortical (HPA) axis of HAA and LAA rats in response to restraint stress. The restraint stress induced an elevation in plasma concentrations of ACTH, prolactin, corticosterone and progesterone. Peak levels of plasma ACTH during stress conditions wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
29
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(31 citation statements)
references
References 24 publications
2
29
0
Order By: Relevance
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance with the present results suggesting that direct adrenal effects of PRL may be important for steroidogenesis in the response to stress, there are observations from animal studies in which glucocorticoid levels can remain elevated during stress, despite de- clining CRH and/or ACTH concentrations [20,21,[40][41][42]. Previous studies have demonstrated that exercise stress induced an increase in circulating PRL in humans [43][44][45][46][47][48].…”
Section: Discussionsupporting
confidence: 91%
“…Selective breeding based on 'high/ low-avoidance' performance was suggested to relate to differences in 'emotional' factors (state/trait anxiety) that influenced performance (Brush, 2003). For example, the 'high-avoidance' and 'low-avoidance' Hatano rat strains did not differ in locomotion activity (Ohta et al, 1999), but the 'low-avoidance' strain had a higher adrenocorticotropin (ACTH)-induced adrenal CORT release response than the 'high-avoidance' strain (Asai et al, 2004). The increased rates of escape failure in the shuttle box that we found among adult juvenilestressed rats (Figure 3c) may also imply an emotional disruption.…”
Section: Exposure To Stress During Juvenility Alters Emotional Responmentioning
confidence: 99%
“…Moreover, our previous reports demonstrated that Haa and Laa have strain differences in locomotor activity and endocrine stress response [2-4, 21, 28, 31]. in brief, Haa shows high activity in running wheel cage [28], high adrenocorticotropin (actH) and low prolactin in plasma during restraint stress compared with Laa [2,4]. but emotional characteristics of Hatano rats have not been investigated yet.…”
Section: Introductionmentioning
confidence: 99%